2022
DOI: 10.1063/5.0091110
|View full text |Cite
|
Sign up to set email alerts
|

Modification of a turbulent boundary layer by circular cavities

Abstract: It is shown how well-chosen perforations in a wall flow can locally reduce skin friction drag by modifying the generation of bursts in the boundary layer. For this purpose, a detailed hot wire experimental boundary layer investigation of the flow past a perforated plate, complemented with large eddy simulations, is carried out and compared to the smooth baseline. The perforated plate is obtained with an array of flush-mounted circular cavities. These cavities are disposed in a periodic staggered arrangement. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
4
7
0
Order By: Relevance
“…From left to right, the figures show a clear reduction in the upward vertical shift at all four measured locations when the Reynolds number increased. This finding agrees with the work by Scarano et al (2022). Scarano et al (2022) also found that the upward vertical shift was more pronounced after the trailing edge of the cavity array, L/d = 125.8, than the one at the array center, L/d = 59.2.…”
Section: Mean Velocity Profilessupporting
confidence: 92%
See 4 more Smart Citations
“…From left to right, the figures show a clear reduction in the upward vertical shift at all four measured locations when the Reynolds number increased. This finding agrees with the work by Scarano et al (2022). Scarano et al (2022) also found that the upward vertical shift was more pronounced after the trailing edge of the cavity array, L/d = 125.8, than the one at the array center, L/d = 59.2.…”
Section: Mean Velocity Profilessupporting
confidence: 92%
“…Figures 7a, 7b, 7d, 7e, 7g, and 7h clearly show an upward vertical shift in the velocity profiles of the turbulent boundary layers over the cavity array in comparison with the ones over a smooth wall at U ∞ = 5.6 and 9.9 m/s at all four measurement locations. This upward vertical shift in turbulent boundary layers over cavities was also found by Silvestri et al (2017) and Scarano et al (2022) and was associated with a reduction in the skin friction drag of turbulent boundary layers using riblets (Choi, 1989). Figures 7c, 7f, 7i, and 7l show that the velocity profiles of the turbulent boundary layers over the cavity array were identical to the one over a smooth wall, which indicates the small effect of the cavity array at U ∞ = 14.2.…”
Section: Mean Velocity Profilessupporting
confidence: 63%
See 3 more Smart Citations